2017
DOI: 10.1364/boe.8.000726
|View full text |Cite
|
Sign up to set email alerts
|

OCT intensity and phase fluctuations correlated with activity-dependent neuronal calcium dynamics in the Drosophila CNS [Invited]

Abstract: Phase-resolved OCT and fluorescence microscopy were used simultaneously to examine stereotypic patterns of neural activity in the isolated Drosophila central nervous system. Both imaging modalities were focused on individually identified bursicon neurons known to be involved in a fixed action pattern initiated by ecdysis-triggering hormone. We observed clear correspondence of OCT intensity, phase fluctuations, and activity-dependent calcium-induced fluorescence. behavior by sequential activation of multiple pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Phase sensitivity ( Δ ) in OCT is intimately linked to SNR, motion (Δx) of the sample, and the spot size ('d') 42,43 as shown in the equation 1 below.…”
Section: Phase Sensitivitymentioning
confidence: 99%
“…Phase sensitivity ( Δ ) in OCT is intimately linked to SNR, motion (Δx) of the sample, and the spot size ('d') 42,43 as shown in the equation 1 below.…”
Section: Phase Sensitivitymentioning
confidence: 99%
“…15,23,57 The fast temporal part of the fOCT signal might also involve neuronal membrane displacements (or deformations) during stimulation, which has been detected with phase-sensitive interferometric or low-coherence imaging techniques. [24][25][26][58][59][60][61] Typically, nanometer-scale displacements were detected on a millisecond time scale and were thought to be caused by the swelling and shrinkage of the nerve fiber 24,25,60 and neural cell bodies. 58,61 Akkin et al 25 reported that the nerve displacements accompanied fast light scattering changes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, fOCT is a potentially attractive tool for detecting electrical activity in neural tissue in vivo. [18][19][20][21][22][23][24][25][26][27] For many studies (e.g., aimed at neuromodulation or functional tract tracing), neural stimulation methods are desirable. Electrical stimulation has been a long-standing tool for neurostimulation, 28,29 but it suffers from spread of electrical current, often leading to unwanted activation of additional brain circuits and resulting side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the popularity of fluorescence imaging, label-free optical detection of action potential (AP) is highly desirable as it eliminates the need to add exogenous chemical or genetic biosensors with inevitable issues associated with photo-bleaching, photo-toxicity, low SNR and the potential of interfering with normal physiological functions. Endogenous optical changes due to action potential propagation can manifest as changes in scattering [14, 31- Reported label-free AP studies using optical techniques have been conducted in drosophila CNS [42], giant squid axon [43,44], lobster [45], and rat-nerve bundle [46,47] models which typically require averaging of multiple optical signals due to poor signal to noise ratio. In recent years, a number of label free optical techniques [14,[31][32][33][34][35][36][37][38][42][43][44][45] based on phase sensitive interferometry have demonstrated detection of neural activity.…”
Section: Introductionmentioning
confidence: 99%